Mechanoresponsive Elastomers Made with Excimer-Forming Telechelics - Kiebala, Derek J.; Fan, Zhiyuan; Calvino, Celine; Fehlmann, Lauren; Schrettl, Stephen; Weder, Christoph (Organic Materials, 2020)
Mechanoresponsive luminescent (MRL) elastomers, which change their fluorescence color or intensity upon deformation, can facilitate simple strain detection through optical signals. Several polymers have been endowed with MRL properties by blending them with excimer-forming dyes, whose assembly and emission color are affected by deformation of the blended materials. However, access to elastic MRL polyurethanes based on this approach has proven difficult and usually requires the covalent incorporation of such dyes in high concentration. Here, we show that much simpler access to MRL elastomers is possible by blending thermoplastic polyurethane elastomers with a small weight fraction of a telechelic sensor macromolecule carrying two excimer-forming oligo(p-phenylene vinylene) dyes at the termini. While the mechanical properties of the two polyurethanes, which were selected because of their dissimilar mechanical behaviors, remain unchanged, the additive imparts these materials with MRL characteristics. Notably, the reliable and reversible detection of strains as low as 5% is possible. The highly sensitive mechanochromic response mirrors the deformation and relaxation processes occurring in these model polyurethanes and enabled a detailed analysis of the processes underlying the shape-memory properties in one of the polyurethanes, in which such behavior was imparted by a crystallizable soft segment.
Keywords: mechanochromic materials; stimuli-responsive materials; organic shape-memory polymers; aggregation